Cardiovascular Reactivity to a Novel Stressor: Differences on Susceptible and Resilient Rats to Social Defeat Stress - Morais-Silva, Gessynger; Gomes-de-Souza, Lucas; Costa-Ferreira, Willian; Pavan, Jacqueline C.; Crestani, Carlos C.; Marin, Marcelo T. (Frontiers in Physiology, 2022)
Prolonged and heightened responses to stress are known factors that influence the development of mood disorders and cardiovascular diseases. Moreover, the coping strategies related to the experience of adverse events, i.e., resilience or the susceptibility to stress, are determinants for the individual risk of developing such diseases. Susceptible rats to the social defeat stress (SDS), identified by the social interaction test (SIT), show behavioral and cardiovascular alterations after SDS exposure that are not found in resilient rats. However, it is not elucidated yet how the cardiovascular system of susceptible and resilient phenotypes responds to a new stressor after SDS exposure. Thus, using the SDS exposure followed by the SIT, we evaluated heart rate, blood pressure, tail skin temperature, and circulating corticosterone responses to an acute session of restraint stress in susceptible and resilient rats to SDS. Susceptible rats showed resting tachycardia and exaggerated blood pressure response to restraint stress, while resilient rats did not present such alterations. On the other hand, both phenotypes showed increased plasma corticosterone and a drop in tail skin temperature to restraint stress, which was similar to that observed in control animals. Our results revealed an increased cardiovascular reactivity in response to a new stressful stimulus in susceptible rats, which might be related to a greater risk for the development of cardiovascular diseases.